Thrombolytic Therapy in Acute Stroke: Outcome, Barriers & How to Overcome - Ahasan, H A M; Hossain, Md. Yeanur; Das, Aparna; Minnat, Baharul; Chowdhury, Mostofa Kamal (Journal of Medicine, 2013)
No Abstract Available DOI: http://dx.doi.org/10.3329/jom.v14i1.14541 J MEDICINE 2013; 14 : 65-69